A scoping review of medication self-management intervention tools to support persons with traumatic spinal cord injury. - Lauren Cadel; Stephanie R Cimino; Glyneva Bradley-Ridout; Sander L Hitzig; Tanya L Packer; Lisa M McCarthy; Tejal Patel; Aisha K Lofters; Shoshana Hahn-Goldberg; Chester H Ho; Sara J T Guilcher (PLoS ONE)
Background Persons with traumatic spinal cord injury (SCI) use multiple medications (polypharmacy) to manage the high number of secondary complications and concurrent conditions. Despite the prevalence of polypharmacy and challenges associated with managing medications, there are few tools to support medication self-management for persons with SCI. Objective The purpose of this scoping review was to identify and summarize what is reported in the literature on medication self-management interventions for adults with traumatic SCI. Methods Electronic databases and grey literature were searched for articles that included an adult population with a traumatic SCI and an intervention targeting medication management. The intervention was required to incorporate a component of self-management. Articles were double screened and data were extracted and synthesized using descriptive approaches. Results Three studies were included in this review, all of which were quantitative. A mobile app and two education-based interventions to address self-management of SCI, medication management, and pain management, respectively, were included. Only one of the interventions was co-developed with patients, caregivers, and clinicians. There was minimal overlap in the outcomes measured across the studies, but learning outcomes (e.g., perceived knowledge and confidence), behavioural outcomes (e.g., management strategies, data entry), and clinical outcomes (e.g., number of medications, pain scores, functional outcomes) were evaluated. Results of the interventions varied, but some positive outcomes were noted. Conclusions There is an opportunity to better support medication self-management for persons with SCI by co-designing an intervention with end-users that comprehensively addresses self-management. This will aid in understanding why interventions work, for whom, in what setting, and under what circumstances.